Amidst glass-walled buildings, a slavic cross: Ukrainians, cultural assets and the city (Tempo e Argumento, 2011)
The purpose of this article is to comment on the venue where Orthodox Ukrainian immigrants settled in the city of Curitiba and to verify strategies adopted in order to preserve ethnic cultural assets during the urbanization of Avenue Candido Hartmann (called the Ukraine Village until 1978). The study of cultural assets and the city is supported by interviews given by immigrants that used to live in the neighborhood, highlighting the dialectic relationship between the venue and the beliefs and cultural practices of this group. If on the one hand urbanity tends to homogenize venues created for a specific purpose, on the other it strengthens ethnic identification in dedicated venues when there is an interest.
Keywords: orthodox church; cultural assets; city